Microorganisms Enhance Understanding of EvolutionReview of: <source>Microbes and Evolution: The World That Darwin Never Saw</source>; edited by <person-group person-group-type="editor"> <name name-style="western"> <surname>Kolter</surname> <given-names>Roberto</given-names> </name> <name name-style="western"> <surname>Maloy</surname> <given-names>Stanley</given-names> </name> </person-group>; ( <year>2012</year>). <publisher-name>ASM Press</publisher-name>, <publisher-loc>Washington, DC</publisher-loc>. <fpage>299</fpage> pages. - Deborah V. Harbour (American Society for Microbiology, 2012)
Review of: Microbes and Evolution: The World That Darwin Never Saw; edited by Roberto Kolter and Stanley Maloy; (2012). ASM Press, Washington, DC. 299 pages